Mapping the global landscape of mental health research: A systematic review of emerging trends, determinants, health policies, and future directions - Tirta Asprimi Angreani; Suprapto Suprapto (Edukasi Ilmiah Indonesia, 2026)
Introduction: Mental health has become a major global public health concern due to its increasing prevalence and its profound social, economic, and healthcare consequences. Although the volume of mental health research has expanded substantially, evidence remains fragmented across disciplines, populations, and thematic areas. This systematic review aimed to map the global landscape of mental health research by identifying emerging trends, key determinants, health policy implications, and future research directions. Research Methodology: A systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. Literature searches were performed in PubMed, Scopus, Web of Science, and Google Scholar for studies published between 2020 and 2025. After duplicate records were removed and eligibility was assessed, 100 studies met the inclusion criteria and were included in the final synthesis. Data were extracted using a standardized form and analyzed through narrative thematic synthesis. Results: From 1,450 records initially identified, 100 studies were included in the final review. The findings revealed four dominant research themes: social and economic determinants (28%), environmental factors (19%), digital technology and mental health (17%), and health policy and service delivery (12%). Socioeconomic disadvantage, housing insecurity, limited social support, and educational and occupational stress emerged as the most frequently reported risk factors. Access to green spaces and community support were consistently associated with improved psychological well-being. The review also identified a growing interest in digital mental health interventions and artificial intelligence applications, while highlighting persistent gaps in policy implementation and equitable access to mental health services. Conclusion: Mental health outcomes are shaped by interconnected social, environmental, technological, and policy-related factors. Effective responses require integrated and multisectoral strategies that address structural determinants while strengthening mental health systems. Future policies should prioritize equitable access to services, community-based interventions, and evidence-informed decision-making to improve mental health outcomes globally